Working Conditions on Digital Labour Platforms: Evidence from a Leading Labour Supply Economy - Mariya Aleksynska; Anastasia Bastrakova; Natalia Nikolaevna Kharchenko (Institute of Labor Economics (IZA), 2019)
Online labour platforms matching labour supply and demand are profoundly modifying the world of work. Businesses use them to outsource tasks to a world-wide pool of workers; while workers can access work opportunities transcending national boundaries. Increasingly, workers are located in developing and transition economies. This paper is based on survey of online workers of Ukraine, which in 2013-2017 occupied the first place in Europe, and the fourth place in the world in terms of the amount of financial flows and the number of tasks executed by workers through online labour platforms. Focusing on working conditions of digital workers, the paper shows that while the majority of these workers are satisfied with their online work, a sizeable proportion faces risk of being in disguised or dependent employment relationship, works informally, and has a poor social protection. The earnings through the platforms are generally comparable to the earnings in the local labour market, but they do undercut payments for equivalent work that could have been performed in other countries. There is an important gender pay gap in online work. The paper also shows how these working conditions are shaped by both local and international business practices of posting tasks on such platforms. Based on these findings, it presents a set of policy reflections, both for Ukraine and for the future global governance in the world of digital work.
Keywords: J2; J3; J4; L2; 330; gig-economy; online labour; digital labour platforms; working conditions